40Ar/39Ar date of a bentonite associated with a methane seep deposit in the upper Campanian Baculites compressus Zone, Pierre Shale, South Dakota. (October 2018) - Landman, Neil H.; Jicha, Brian R.; Cochran, J. Kirk; Garb, Matthew P.; Brophy, Shannon K.; Larson, Neal L.; Brezina, Jamie
Abstract: 40 Ar/ 39 Ar dating of a bentonite associated with a cold methane seep deposit in the upper Campanian Baculites compressus Zone of the Pierre Shale in South Dakota yields an age of 73.79 ± 0.36 Ma. This is in close agreement with the previously published age of 74.05 ± 0.39 Ma for this zone (Obradovich, 1993) and nearly identical to an unpublished age of 73.70 ± 0.13 Ma for the same zone, both samples of which are from a more proximal locality near the base of the Bearpaw Shale in Montana, as recalculated relative to a Fish Canyon standard age of 28.201 Ma. We also report dates for two bentonites from the upper Campanian Exiteloceras jenneyi and Didymoceras stevensoni zones.